Global intellectual property protection and new constitutionalism : hedging exclusive rights - Griffiths, Jonathan, 1965-; Mylly, Tuomas (Oxford : Oxford University Press, 2021)
This collection of essays, written by international experts and covering a range of different areas of intellectual property law, draws on constitutional theory, and particularly on ideas of 'new constitutionalism', to engage with the complex array of contemporary legal constraints on intellectual property law-making.
This edition also issued in print: 2021.
"This is an open access publication, available online and distributed under the terms of a Creative Commons Attribution - Non Commercial - No Derivatives 4.0 International licence (CC BY-NC-ND 4.0)"--Home page.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on November 15, 2021).
Keywords: Intellectual property; Constitutional law; Law; Laws of specific jurisdictions & specific areas of law